PELATIHAN PIJAT BAYI KEPADA KADER POSYANDU DESA MABUNG KECAMATAN BARON KABUPATEN NGANJUK - Dewi Kartika Sari; Halimatus Saidah (Jurnal Abdi Masyarakat, 2020)
ABSTRACTBaby massage is a relaxation technique that has been practiced for generations in Indonesia.The problem found in partners is the lack of knowledge of Posyandu activities about theimportance of baby massage and how to massage babies properly and correctly, while thePosyandu activities is an important person for the community because as one of the communitymobilizers in maternal and child health and family planning, therefore the cadre need to gettraining about baby massage. The objectives of this activity are to improve the quality of thebaby's health and increase Posyandu activities knowledge about baby massage. The methodthat will be carried out in this activity is the identification of Posyandu activities' knowledge ofinfant massage then training Posyandu activities on the importance of baby massage and theimplementation of baby massage properly and correctly with the number of participants is 23participants. Based on the results of the training, there was an increase in Posyandu activitiesknowledge about baby massage and Posyandu activities became aware of how to massagebabies properly. This is expected to be implemented in society so that the welfare of the babyincreases.Key word : Posyandu activities, baby, baby massageABSTRAKPijat bayi adalah sebuah teknik relaksasi yang telah turun temurun dipraktekkan diIndonesia. Permasalahan yang ditemukan pada mitra adalah masih rendahnya pengetahuankader tentang pentingnya pijat bayi serta cara memijat bayi dengan baik dan benar, sedangkankader merupakan orang yang penting bagi masyarakat karena sebagai salah satu penggerakmasyarakat dalam kesehatan ibu dan anak serta KB, maka dari dari itu kader perlumendapatkan pelatihan tentang pijat bayi. Tujuan yang ingin dicapai dari kegiatan ini adalahmeningkatkan kualitas kesehatan bayi dan meningkatkan pengetahuan kader tentang pijat bayi.Metode yang akan dilaksanakan pada kegiatan ini adalah identifikasi pengetahuan kadertentang pijat bayi kemudian melakukan pelatihan kepada kader tentang pentingnya pijat bayi.Berdasarkan hasil pelatihan, terdapat peningkatan pengetahuan kader tentang pijat bayi dankader menjadi mengerti tentang cara memijat bayi dengan baik dan benar.